2018
DOI: 10.1007/s11575-018-0367-x
|View full text |Cite
|
Sign up to set email alerts
|

What Fosters Individual-Level Absorptive Capacity in MNCs? An Extended Motivation–Ability–Opportunity Framework

Abstract: Absorptive capacity has been marked as one of the most important capabilities of Multinational Corporations for effective management of knowledge. To address calls for research on micro-level origins of the concept, this paper focuses on the determinants of individual-level absorptive capacity. We examine the extent to which individuals' capability to recognize, assimilate and exploit new knowledge from the environment is shaped by different forms of work motivation (i.e., intrinsic and extrinsic), overall abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 133 publications
(197 reference statements)
7
47
0
1
Order By: Relevance
“…Such characteristics are in line with the early findings of ESM's use that focused on its potential to identify and interact with relevant external information [14]. Prior studies in the field of knowledge management indicate that successful knowledge management depends on opportunities [21,22]. The opportunities for transferring knowledge often reside in social relationships [23,24] that can be Sustainability 2020, 12, 2855 3 of 32 enhanced by ESM's visibility.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Such characteristics are in line with the early findings of ESM's use that focused on its potential to identify and interact with relevant external information [14]. Prior studies in the field of knowledge management indicate that successful knowledge management depends on opportunities [21,22]. The opportunities for transferring knowledge often reside in social relationships [23,24] that can be Sustainability 2020, 12, 2855 3 of 32 enhanced by ESM's visibility.…”
Section: Introductionsupporting
confidence: 65%
“…Collaboration visibility affords individuals the opportunity to visualize various ways of digesting contradictory knowledge, exploring different perspectives of problem solving, and helping them generate new ideas [88], so that they know how to apply the retained external knowledge. External knowledge is novel and diverse compared with the knowledge they already have [22]. The diversity of external knowledge will drive continuous innovations for internal applications, allowing workers to easily apply newly acquired knowledge to possible areas.…”
Section: The Relationship Between Collaboration Visibility and The Prmentioning
confidence: 99%
“…AS step is fundamental to transform information into knowledge, for both individual development and rural property management. To summarize, we can mention Hotho et al (2012), Minbaeva et al (2014) and Yildiz et al (2019), who assert that individuals play a crucial role in the absorption and transfer of knowledge.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…and Yildiz et al (2019) since it expands studies in the field of IAC. In addition, it has been shown that the study presents potential empirical gains, since the association between the constructs suggests an important source of competitive advantage for the rural properties, offering elements for cooperative managers to formulate strategies to help in the preparation of the rural successors' dilemma.…”
Section: Final Considerationsmentioning
confidence: 92%
See 1 more Smart Citation